Utility relocation management in highway projects. Issue 2 (13th April 2018) - Vilventhan, Aneetha; Kalidindi, Satyanarayana N.
Abstract : Purpose: Utility relocation issues are unfortunately frequent and recurring problems in several countries' highway projects. Very few studies have addressed the utility relocation issues in highway projects. The purpose of this paper is two-fold. First, this paper explores how the utility relocation issues are managed in highway projects. Second, this paper systematically identifies the prioritized technical and coordination strategies to be adopted to avoid delays in utility relocation. Design/methodology/approach: Multiple case-based research methodology was used to explore how the utility relocation issues are managed in highway projects. Empirical evidences from 11 road and bridge projects in India were used to develop the descriptive storyline for each of the project. The strategies used to manage the utility relocation issues were identified from three sources namely literature review, case studies and nominal group technique (NGT). The strategies were then evaluated quantitatively using NGT. Findings: The analysis of the case studies showed that the delays in utility relocation were in the range of 5-52 months. It was found that the duration of relocation of utilities is impacted more significantly by the complexity of underground utilities rather than the size of the projects. Strategies that are used to manage utility relocation were identified across two groups namely; technical and coordination strategies. Practical implications: Recommendations are provided for the practical use and policy changes. Originality/value: The prioritized technical and coordination strategies can be used systematically to avoid delays in utility relocation.